The rule of law, the community based on the rule of law, and the judicial system of the Andean Community - Mendoza Neyra, Yolanda (2025)
At a time of various national crises and new global challenges that put the Andean Community’s security and integrity at risk, its member countries seek, above all, to protect themselves with their weak democracies, precarious institutional systems and contradictory national legal systems. These state actions, which largely reflect the rule of law´s deficiency in the member countries, causes infringement of Andean community law, reiterate lack of interest in consolidating Andean integration, violate human rights, and, above all, disregard our supranational organization’s community of law based on the rule of law. To reverse this situation, in this article, we propose that the judicial system of the Andean Community be in charge of preserving the Member Countries’s rule of law and strengthening the Andean Community’s community of law based on the rule of law, through new judicial mechanisms. This will facilitate the development more comprehensive and specific jurisprudence on the community of law based on the rule of law, as well as its relationship with the Andean Community’s principles, especially with the rule of law, democracy, and human rights.